FUNGSI DAN MAKNA DRAMA TARI PACALONARANGAN DALAM UPACARA SUDHAMALA BHUMI PRATISTHA DI DESA PAKRAMAN SESETAN - Indra Wirawan, I Komang (PANGKAJA, 2012)
Pacalonarangan Ballet is a theatrical art which is a unification of dance, drama and literature supported by fine arts such as sculpture, decorative art, painting, etc. The term of calonarang, besides as a literary work, means a figure or a name of person in the story named Ni Calonarang. Calonarang is also found in the forms of work of art such as wayang (shadow play) pacalonarangan and in the theatrical art of ballet called Pacalonarangan Ballet. The calonarang story in Pacalonarangan is not releted yet to the common calonarang story. It is a piece of babad: Basur, or Ki Balian Batur, which contains mystical elements. In the calonarang performance, the story shows fighting between the power of black and white magic which are simbolyzed by: pangundangan (inviting), pangerehan (trance), watangan hidup (living corpse), traktakan linggih ratu ayu, pepatih, Rangda (the throne of queen, ministers, and Rangda (the goddess).Pacalonarangan Ballet in Sudhamala Bhumi Pratistha in Sesetan village aims at guiding Sesetan villagers’ understanding in order to strengthen their faith (sradha) to God. People consider pandemic the act of devil spirit or power which is hard to overcome by human. One of people’s efforts is to pray for safety and being avoided from dificulty. As the form of their gratitude, the people of Sesetan village hold Sudhamala Bhumi Pratistha ceremony. The ballet is the reflection of the ceremony. Last, the meaning of Pacalonarangan ballet; they are theologic meanings including Panca Durga as the symbol of darkness, power and nature. They are also to discusses about the meaning of aesthetic, education, and harmony implied in the cheremony. Through its symbols, it is expected that the ceremony could be the reflection of the life itself creating balance of macro and micro cosmos resulting in true happiness.Key words : Drama tari Pacalonarangan, Sudhamala Bhumi Pratistha